Thermodynamic analysis circulating heating method pitch of the bowl - Яковлєва, Ірина Геннадіївна; Назаренко, Ірина Анатоліївна; Кюрчева, Дар’я Петрівна (Eastern-European Journal of Enterprise Technologies, 2012)
This paper presents a thermodynamic analysis of the effectiveness of the circulation method of heating the pitch. The main indicator of the degree of thermodynamic perfection of the process is the exergy efficiency (efficiency) ηeks